2007
DOI: 10.1038/sj.npp.1301654
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Subchronic PCP-Induced Deficits in Attentional Set Shifting in Rats by Sertindole and a 5-HT6 Receptor Antagonist: Comparison Among Antipsychotics

Abstract: Currently accepted treatments for schizophrenia can effectively control positive symptoms but have limited impact on cognitive deficits in schizophrenia. The purpose of these experiments was to address this unmet need by characterizing the effects of classical and secondgeneration antipsychotics on cognitive impairments associated with schizophrenia. An additional aim was to characterize the part(s) of the pharmacological profile of drugs that were important to reverse deficits. Cognitive deficits were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
99
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 65 publications
13
99
2
Order By: Relevance
“…In contrast, Rodefer and colleagues subsequently found that clozapine and risperidone to be ineffective in reversing the PCP-induced deficit, however sertindole and the selective 5-HT 6 (SB-271046) and 5-HT 2A (M100907) receptor antagonists did attenuate the PCP-induced impairment (Rodefer et al, 2008), which is similar to our findings using reversal learning paradigm (Idris et al 2010). This same dosing regime was shown again in male hooded-Lister rats to produce deficits in the EDS phase; an effect which was ameliorated by sertindole and the anti-narcoleptic drug modafinil but not by risperidone or haloperidol (Goetghebeur and Dias, 2009).…”
Section: Attentional Set-shiftingsupporting
confidence: 86%
“…In contrast, Rodefer and colleagues subsequently found that clozapine and risperidone to be ineffective in reversing the PCP-induced deficit, however sertindole and the selective 5-HT 6 (SB-271046) and 5-HT 2A (M100907) receptor antagonists did attenuate the PCP-induced impairment (Rodefer et al, 2008), which is similar to our findings using reversal learning paradigm (Idris et al 2010). This same dosing regime was shown again in male hooded-Lister rats to produce deficits in the EDS phase; an effect which was ameliorated by sertindole and the anti-narcoleptic drug modafinil but not by risperidone or haloperidol (Goetghebeur and Dias, 2009).…”
Section: Attentional Set-shiftingsupporting
confidence: 86%
“…The D 1 antagonist used in these studies (SCH23390) has affinity for both D 1 and 5HT 2A receptors. However, the observation that systemic blockade of 5HT 2A receptors with M100907 produces no apparent impairment in set-shifting (Rodefer et al, 2008) suggests that the effects of SCH23390 reported here are likely attributable to actions on NAc D 1 receptors.…”
Section: A Selective Role For Nac D 1 Receptors In Strategy Set-shiftingmentioning
confidence: 53%
“…It has been reported that haloperidol is ineffective whereas risperidone, olanzapine, and clozapine show nonsignificant trends toward improved ED-shift performance, and other antipsychotics, sertindole, and quetiapine show full reversal (Rodefer et al, 2008;Goetghebeur and Dias, 2009;Nikiforuk and Popik, 2012). In addition, studies of selective 5-HT receptor subtype antagonists indicate that the 5-HT 2A antagonist M100907 has borderline effects similar to risperidone whereas a 5-HT 6 antagonist [SB-271046, 5-chloro-N-[4-methoxy-3-(1-piperazinyl) phenyl]-3-methylbenzo[b]thiophene-2-sulfonamide hydrochloride] and 5-HT 7 antagonist [SB-269970, (R)-3-{2-[2-(4-methylpiperidin-1-yl)ethyl]pyrrolidin-1-ylsulfonyl}phenol] replicate the profile of sertindole (Rodefer et al, 2008;Nikiforuk et al, 2013). Therefore, the effect of brexpiprazole in this model would be associated with its potent 5-HT 2A and modest 5-HT 6 receptor antagonist activity (Maeda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Subchronic PCP treatment is known to impair cognitive performance in various tests (Rodefer et al, 2008;Neill et al, 2010). Two tests were selected for characterization of brexpiprazole and aripiprazole in the present studies: NOR and ID-ED.…”
Section: Brexpiprazole Reverses Cognitive Deficits Induced By Subchromentioning
confidence: 99%
See 1 more Smart Citation